2004
DOI: 10.1038/sj.bjc.6601519
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of a psychoeducational intervention for women at increased risk of breast cancer

Abstract: This study aimed to compare the impact of two versions of a psychoeducational written intervention on cancer worry and objective knowledge of breast cancer risk-related topics in women who had been living with an increased risk of familial breast cancer for several years. Participants were randomised to three conditions: scientific and psychosocial information pack (Group 1), scientific information pack only (Group 2) or standard care control (Group 3). They completed postal questionnaires at baseline (n ¼ 163… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Various methods of education, including personal counselling, written information and computer programmes have been shown to improve knowledge on breast cancer genetics, but the effect on interest in testing is less clear [17,20,23,26,[28][29][30]. We now present the results of a large randomised study assessing the effects of educational information on interest in BRCA1 genetic testing in women at increased risk of breast cancer and women with breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Various methods of education, including personal counselling, written information and computer programmes have been shown to improve knowledge on breast cancer genetics, but the effect on interest in testing is less clear [17,20,23,26,[28][29][30]. We now present the results of a large randomised study assessing the effects of educational information on interest in BRCA1 genetic testing in women at increased risk of breast cancer and women with breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Kash et al (1995) reported a randomised controlled trial of a 1-year group intervention, describing a reduced perception of risk and an increased adherence to screening behaviours and in knowledge about participants' high-risk status. In a psychoeducational written intervention consisting of an educational and psychosocial pack, Appleton et al (2004) also found postintervention benefits in terms of diminished cancer worry and improved BRCA risk-related information. Karp et al (1999) described a psychoeducational programme reporting prophylactic mastectomy issues in a group of BRCA carriers, and Speice et al (2002) conducted a six-session psychoeducational intervention focusing on family-related themes.…”
Section: Introductionmentioning
confidence: 93%
“…Psychoeducational written material including information on scientific and psychosocial aspects of familial risk for cancer may also be distributed, as described in the study of Appleton et al (2004).…”
Section: Learning From Our Experiencementioning
confidence: 99%
“…18,19 However, only a small percentage of individuals who may benefit from a greater understanding of their risk for cancer actually undergo genetic counseling. Further, much of the research has focused on the individual's perception and understanding of their own risk and how they convert complex information into something understandable that will inform their decisions, 18,20,21 with little attention to family's perceptions and concerns.…”
Section: Cancer Risk Information and Educationmentioning
confidence: 99%